BIOAKTIVITAS EKSTRAK SARANG SEMUT Myrmecodia pendens TERHADAP RAYAP TANAH Coptotermes curvignathus Holmgren - Muhammad Ramadhan Dwi; . Nurhaida (Tengkawang : Jurnal Ilmu Kehutanan, 2018)
Myrmecodia pendens are epiphytic plants which known as herbal plants in some region in Indonesia. The purpose of this study was to examine Myrmecodia pendens extracts with different concentrations against subterranean termites Coptotermes curvignathus Holmgren. The research was conducted at the Wood Technology Laboratory, Forestry Faculty, Tanjungpura University for three months. Myrmecodia pendens was from Maluku Island. 50 gram Myrmecodia pendens was extract with methanol with ratio 1:3,  then the extract was made into five concentrations i.e. 2%, 4%, 6%, 8% and 10%. Filter paper then dipped into the extract solution and used for food substrates of termites. The bioassay was conducted for 21 days in termite’s chamber room. Each treatment has three replications. The indicator used for evaluate the effectiveness of the extract was termites mortality and filter paper weight loss. The results showed the rendemen of Myrmecodia pendens extract was 24.1888 gram (23.1576%). The average value of termite’s mortality was 67.33% - 100.00%. The concentration of 2% has termites mortality values of 67.33% and included in the category of strong levels of anti-termite activity. The highest termite’s mortality value was achieved on concentration of 10%. The average value of filter paper weight loss was 33.54% – 65.27%. The highest concentration of the extracts resulted in the lowest filter paper weight loss. Meanwhile on control treatment the average values of termites mortality was 14.67% and the filter paper weight loss was 73.22%. The extract Myrmecodia pendens was effectives to inhibition the subterranean termites attacks. The optimum concentration of Myrmecodia pendens extract was achieved at concentration 6% with termites mortality value was 78% with category of very strong levels of anti-termite activity.Keywords : antitermites, Coptotermes curvignathus, Myrmecodia pendens, preservation